A multiple case study of coordinated care for children with IBD through caregiver interviews. (December 2020) - deJong, Neal A; Vu, Maihan B; Cui, Jiawei; Dole, Michael; Moulton, Dedrick E; Kappelman, Michael D
Introduction: Effective care coordination is critical to manage unpredictable complications of conditions such as pediatric inflammatory bowel disease (IBD) that have a relapsing and remitting course. Our objective was to explore perspectives of care coordination following emergency department (ED) visits by children with IBD, because these may indicate deficient care coordination. Methods: Using a multiple case study approach, we sought perspectives through semi-structured interviews of caregivers (parents, primary care providers, and gastroenterologists) for children with IBD who had a recent ED visit in either of two large pediatric referral centers in the southeastern US. We used criterion sampling to identify eligible participants through a medical record report of ED visits, and iterative sampling concurrent with analysis until no new themes were identified. Interviews were transcribed verbatim, and transcripts were coded using directed content analysis to identify emergent themes. Results: From twenty-six interviews, three major themes emerged: perceptions of appropriate expertise, desire for integration of information and services, and making assumptions instead of engaging. Participants describe distinct roles for primary care and gastroenterology providers and recognize communication and information barriers to better coordination. Some parents and gastroenterologists perceive challenges to engaging primary care providers. Common recommendations include explicit guidance from gastroenterologists to primary care providers and methods for direct communication. Discussion: Stakeholders describe common barriers and facilitators for effective care coordination, but some express beliefs about provider roles that could hinder improvement efforts. Tools to support asynchronous communication and shared planning may improve coordination and care quality for complications of IBD.